The PROVIDERS [Preferred Reporting of Variables in Implant Dentistry Education and Research Studies] checklist - Bibi Fatima; Khan, Farhan Raza; Kazmi, Syed Murtaza Raza (Journal of the Pakistan Medical Association, 2026)
Implant dentistry is an evolving field. Variability in study designs, outcome measures and reporting standards among the implant dentistry research papers create challenges for the comparability and reproducibility of research findings. To mitigate these challenges, a Preferred Reporting of Variables in Implant Dentistry Education and Research Studies checklist is being proposed, which provides identifying the variables that are essential in the reporting of dental implant-based studies. The objective is to propose comprehensive recommendations to enhance transparency, quality and consistency in reporting dental implant-related research. This checklist will not only standardise the key methodological details across studies and post-implant care, but will also facilitate an easier data synthesis for meta-analyses in the future by addressing potential challenges related to inconsistency in the ‘effect size measures’, making it invaluable for the researchers and clinicians. The proposed checklist would function as a teaching tool in educational settings, fostering evidence-based practice and improving the reproducibility of research in implant dentistry. Key Words: Dental implants, Education, Research.